THE HUMAN CAPITAL THEORY AS A METHODOLOGICAL FOUNDATION OF CONTINUOUS VOCATIONAL EDUCATION - Nellia Nychkalo (National Academy of Educational Sciences of Ukraine, 2018)
The human capital theory is considered based on the interdisciplinary approach from three perspectives - individual, microeconomic and macroeconomic. The contemporary approaches to the implementation of the state policy on vocational education are analysed. It is given a comprehensive overview of the main vocational education mission - to provide preparation of the younger generation to employment and different adult population categories with continuous professional development. It requires forecasting - technological, demographic, economic and political (according to D. Bell). It is considered the problems of self-actualization and professional identity treated as a basis for human capital development. It has been proven that a methodological foundation of a theoretical analysis of personality self-actualization in professional life is formed based on the subjective and pragmatic, personality developing and acmeological approaches. It is stressed the importance of using the occupational prestige monitoring results (based on Traiman's International Occupational Prestige Scale) in scientifically substantiated forecast of labour market changes and forward-looking modernization of the vocational training system. An emphasis is placed on the importance of the Ukrainian scholars' works (S. Goncharenko, I. Ziaziun, G. Kostiuk, V. Kremen, S. Maksymenko, V. Moliako, D. D. Thorzhevskiy) for implementation of the forwardlooking approach in vocational training modernization. It is made the original recommendations for the state policy on this issue at the nationwide, regional, field and academic research levels. Some attention is given to the European strategy "Europe 2020" that is of critically importance not only for the UE Member-States but also for candidate countries.